Educational Strategies Employed by Successful SMEs in KwaZuluNatal - Gavin A. Chapman (Foxton Books, 2019)
Successful SMEs in KwaZulu-Natal do not all follow formal or 'classical' strategic planning methodologies taught by most business schools. While many SMEs collapse within the first year of operation, others become successful in their endeavours to firstly make a living for themselves and secondly to employ others in order to improve and uplift the economy of South Africa. In this qualitative study, four business models were selected which are taught at most business schools. All SMEs engaged in this study acknowledged the value of using business models to support strategic planning. The medium size enterprises did prepare formal strategic plans and monitored all their activities on a regular basis. Small size SMEs use a mixture of business 'creativity' to accommodate uncertain economic conditions and make quick decisions and have been able to succeed even during poor economic times. A new concept called 'extremely flexibile' strategic planning was introduced to enable small size SMEs to consider an alternate method of making strategic plans in a less-structured manner.